2014
DOI: 10.1111/apt.12746
|View full text |Cite
|
Sign up to set email alerts
|

Idarubicin‐loaded beads for chemoembolisation of hepatocellular carcinoma: results of the IDASPHERE phase I trial

Abstract: Using drug-eluting beads, the maximum-tolerated dose of idarubicin was 10 mg per TACE session. Encouraging responses and median time to progression were observed. Further clinical investigations are warranted (NCT01040559).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 35 publications
1
34
1
1
Order By: Relevance
“…Immediately after injection of the emulsion, we did not detect any idarubicin in the plasma; it took at least a few minutes for the drug to appear. When compared with data in the literature, our findings highlighted the improved PK profile of idarubicin c-TACE compared with both doxorubicin c-TACE (mean C max 10 times lower [7]) and idarubicin IV injection (mean AUC 0-24h three times lower [33]), and also showed that the in vivo release of idarubicin from a lipiodol-based emulsion was very close to that observed from DEEs [23,34] (Table 4). The first peak of idarubicinol concentration between 5 and 10 min after injection of the emulsion can be explained by the very quick extraction of part of the idarubicin by hepatocytes followed by its immediate metabolisation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Immediately after injection of the emulsion, we did not detect any idarubicin in the plasma; it took at least a few minutes for the drug to appear. When compared with data in the literature, our findings highlighted the improved PK profile of idarubicin c-TACE compared with both doxorubicin c-TACE (mean C max 10 times lower [7]) and idarubicin IV injection (mean AUC 0-24h three times lower [33]), and also showed that the in vivo release of idarubicin from a lipiodol-based emulsion was very close to that observed from DEEs [23,34] (Table 4). The first peak of idarubicinol concentration between 5 and 10 min after injection of the emulsion can be explained by the very quick extraction of part of the idarubicin by hepatocytes followed by its immediate metabolisation.…”
Section: Discussionsupporting
confidence: 68%
“…The removal of embolisation from TACE did not significantly decrease survival in the study [28], thereby highlighting the major role of the anticancer drug in the efficacy of the procedure. Idarubicin demonstrated higher cytotoxicity in vitro compared with 10 other anticancer drugs [18], and the drug has already shown both its clinical safety and its efficacy through a phase I DEE-TACE trial [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, two first-in-human studies of lipiodol-TACE using idarubicin and of idarubicin-loaded DEBs were performed in unresectable HCC patients [5,8]. Unfortunately, despite encouraging safety profile, these studies failed to demonstrate any superiority of idarubicin on time to progression and overall survival in comparison with the previous published data on TACE using doxorubicin.…”
Section: Based On Preclinical In Vitro Studies That Demonstrated Supementioning
confidence: 97%
“…An important limitation of conventional TACE is that the technique and treatment schedules can be heterogeneous from one unit to another and this makes the results reported in the literature very inconsistent [3]. For these reasons, TACE with drugeluting beads (DEBs) (commonly doxorubicin, cisplatin, epirubicin and more recently idarubicin) has increasingly been performed interchangeably with conventional TACE in many institutions throughout the world, as a novel technique capable of ensuring more sustained and tumorselective drug delivery and permanent embolization [4,5]. However, previous comparisons between TACE with DEBs and conventional TACE with lipiodol in intermediate-stage HCC demonstrated only slightly conflicting results.…”
mentioning
confidence: 99%